2023
DOI: 10.1002/adma.202305344
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed Hydrogen‐Bonded Organic Framework Nanofilms for High‐Performance Resistive Memory Devices

Abstract: The integration of hydrogen‐bonded organic frameworks (HOFs) into electronic devices holds great promise due to their high crystallinity, intrinsic porosity, and easy regeneration. However, despite their potential, the utilization of HOFs in electronic devices remains largely unexplored, primarily due to the challenges associated with fabricating high‐quality films. Herein, we achieved controlled synthesis of HOFs nanofilms with smooth surface, good crystallinity, and high orientation using a solution‐processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In order to analyze the device-to-device variation and reproducibility, the distribution of set/reset voltage and HRS/LRS currents in 10 × 10 memristor array is shown in Figure S15. It suggested the reliability and repeatability of our artificial memristor equivalent to other reported organic/inorganic memristors. For the Al/PbiAz/ITO device, the negative bias of −0.85 V switched the device from the OFF state to the ON state. Subsequently, the positive bias of 2.7 V reset operations and achieved the ON/OFF current ratio of approximately 44 (Figure S16a).…”
Section: Results and Discussionsupporting
confidence: 59%
“…In order to analyze the device-to-device variation and reproducibility, the distribution of set/reset voltage and HRS/LRS currents in 10 × 10 memristor array is shown in Figure S15. It suggested the reliability and repeatability of our artificial memristor equivalent to other reported organic/inorganic memristors. For the Al/PbiAz/ITO device, the negative bias of −0.85 V switched the device from the OFF state to the ON state. Subsequently, the positive bias of 2.7 V reset operations and achieved the ON/OFF current ratio of approximately 44 (Figure S16a).…”
Section: Results and Discussionsupporting
confidence: 59%
“…The thermal and solvent stability of crystals indicated that SSBUs built by charged-assisted 70 supramolecular clusters stabilized TCA_NH 4 and avoided further phase change 71 and collapse of the framework. Taking advantage of the solution-processible benefit of HOFs 72 , the encapsulated trihalomethane could be decapsulated by mild hydrolysis of hydrogen-bonded networks. After heating and dissolving in dimethyl sulfoxide (DMSO), nuclear magnetic resonance (NMR) results revealed that the encapsulated TCA_NH 4 @CHCl 3 , TCA_NH 4 @CHBr 3 , and TCA_NH 4 @CHI 3 were observed to decompose and trihalomethane were observed to release (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ON/OFF ratio can be calculated as 1.96 × 10 2 using −0.1 V as the reading voltage. The relatively low voltage can avoid device failure, which was commonly adopted in memory devices. ,, The uniform HRS/LRS currents and V set / V reset distributions with 10 sweeping cycles hint that its binary resistive switching behavior is repeatable (Figure S7b,c). The device endurance could be further verified by 100 continuous cycles (Figure S7d).…”
Section: Resultsmentioning
confidence: 99%